4x*4x+19x+21=0

Simple and best practice solution for 4x*4x+19x+21=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x*4x+19x+21=0 equation:


Simplifying
4x * 4x + 19x + 21 = 0

Reorder the terms for easier multiplication:
4 * 4x * x + 19x + 21 = 0

Multiply 4 * 4
16x * x + 19x + 21 = 0

Multiply x * x
16x2 + 19x + 21 = 0

Reorder the terms:
21 + 19x + 16x2 = 0

Solving
21 + 19x + 16x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
16 the coefficient of the squared term: 

Divide each side by '16'.
1.3125 + 1.1875x + x2 = 0

Move the constant term to the right:

Add '-1.3125' to each side of the equation.
1.3125 + 1.1875x + -1.3125 + x2 = 0 + -1.3125

Reorder the terms:
1.3125 + -1.3125 + 1.1875x + x2 = 0 + -1.3125

Combine like terms: 1.3125 + -1.3125 = 0.0000
0.0000 + 1.1875x + x2 = 0 + -1.3125
1.1875x + x2 = 0 + -1.3125

Combine like terms: 0 + -1.3125 = -1.3125
1.1875x + x2 = -1.3125

The x term is 1.1875x.  Take half its coefficient (0.59375).
Square it (0.3525390625) and add it to both sides.

Add '0.3525390625' to each side of the equation.
1.1875x + 0.3525390625 + x2 = -1.3125 + 0.3525390625

Reorder the terms:
0.3525390625 + 1.1875x + x2 = -1.3125 + 0.3525390625

Combine like terms: -1.3125 + 0.3525390625 = -0.9599609375
0.3525390625 + 1.1875x + x2 = -0.9599609375

Factor a perfect square on the left side:
(x + 0.59375)(x + 0.59375) = -0.9599609375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| x^2+8x-105= | | 3x+12-6x=18-14x+11x-6 | | 10-(2y-5)=8-3y | | 3x^2+6x+10=y | | 62/-10 | | x*x+16x-4=9x+4 | | 5x-3(x-4)=-6+5x+12 | | 32-6y+7y=-15+28 | | x*x+11x+31=7 | | a^2+8a-33= | | 2cs-17=a | | y^2-2y-16x+49=0 | | 37/y*4/7=74/35 | | 2x-6/4+x+5/6 | | 4(c+4.3)=6(c+1.8) | | -1/2(x-6)=3x | | -6-9r=-10r | | a=p+rt | | x*x-6x-40=0 | | M/19-1=-2 | | 13x-7+3x-4=12x-3+3 | | 8(-6b+5)=328 | | 7(b-0.5)=2(b+4.5) | | s+5/2s+20=48 | | -6n+9=-9n | | 8y-4y=-2 | | x-4/4+2=5 | | 2xz-4-z=4 | | 2(t-11)=26 | | 5m+10=0 | | a^2+6a-55= | | 5g+6=7g |

Equations solver categories